2020
DOI: 10.3390/s20226653
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Film Flexible Wireless Pressure Sensor for Continuous Pressure Monitoring in Medical Applications

Abstract: Physiological pressure measurement is one of the most common applications of sensors in healthcare. Particularly, continuous pressure monitoring provides key information for early diagnosis, patient-specific treatment, and preventive healthcare. This paper presents a thin-film flexible wireless pressure sensor for continuous pressure measurement in a wide range of medical applications but mainly focused on interface pressure monitoring during compression therapy to treat venous insufficiency. The sensor is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Based on Ecoflex, the sensitivity of the sensor obtained through the experiment is higher than that achieved by simulation, mainly due to the difference between the material parameters in the simulation and the actual situation. The flexible LC pressure sensor designed based on Ecoflex material in this paper not only has higher pressure sensitivity than most sensors reported in the existing works (as shown in Table 2) but also fits human skin well and has higher wearing comfort compared to the sensors based on PI substrate and PDMS substrate [20,29].…”
Section: Pressure Sensitivity Test Of the Flexible Lc Pressure Sensormentioning
confidence: 85%
See 1 more Smart Citation
“…Based on Ecoflex, the sensitivity of the sensor obtained through the experiment is higher than that achieved by simulation, mainly due to the difference between the material parameters in the simulation and the actual situation. The flexible LC pressure sensor designed based on Ecoflex material in this paper not only has higher pressure sensitivity than most sensors reported in the existing works (as shown in Table 2) but also fits human skin well and has higher wearing comfort compared to the sensors based on PI substrate and PDMS substrate [20,29].…”
Section: Pressure Sensitivity Test Of the Flexible Lc Pressure Sensormentioning
confidence: 85%
“…The flexible LC pressure sensor designed based on Ecoflex material in this paper not only has higher pressure sensitivity than most sensors reported in the existing works (as shown in Table 2 ) but also fits human skin well and has higher wearing comfort compared to the sensors based on PI substrate and PDMS substrate [ 20 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research revealed that the 10-100 MHz operating frequencies are safe for in vivo wireless measurements [27]. The sensitivity of the LC-MEMS pressure sensor from previous studies was in the range between 2 to 162 kHz/mmHg [16][17][18][19][20][21][22]25,28]. However, sensitivity values at higher rates are required for more accurate and precise measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this Special Issue of Sensors is to provide an open collection of state-of-the-art investigations on wearable and nearable biosensors and systems in order to foster further technological advances and the use of the technology to benefit healthcare. The 12 papers that constitute this Special Issue offer both depth and breadth pertaining to wearable and nearable technology [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Depth is afforded through a critical mass of studies on accelerometers [ 3 , 4 , 5 , 7 , 9 , 10 ], signal processing [ 1 , 2 , 4 , 5 , 7 , 10 , 11 ], and cardiovascular monitoring applications [ 2 , 5 , 6 , 7 , 9 , 10 , 12 ], whereas breadth is given through new biosensors [ 12 ] and data transmission [ 9 ], other clinical applications including surgical training [ 8 ] and brain-computer interfaces [ 1 ], and validation of commercial devices [ 6 ], which is crucial for adoption.…”
mentioning
confidence: 99%
“…Farooq et al [ 12 ] developed a thin-filmed flexible wireless pressure sensor for interface pressure monitoring during leg compression treatment of venous insufficiency. The sensor is based on a pressure-dependent capacitance and inductive coil to allow passive and wireless measurement.…”
mentioning
confidence: 99%